The Eudemonic Wellbeing of Volunteers in a Public Health Emergency: COVID-19 in China - Tang, Juan; Li, Xiao-chen; Zhang, Xi (Frontiers in Psychology, 2022)
With improvements in the public awareness regarding volunteer opportunities, more people are participating in social work, particularly during emergency events. The mental health of volunteers has been attracting more academic attention due to its increasing social significance. Drawing on the Theory of Planned Behavior, a qualitative interview was conducted to identify important attitudes, subjective norms, and perceived control factors guiding people’s volunteering behaviors in an emergency context. Then, a sequential quantitative survey was implemented based on the results of the qualitative study to explore the impact of the aforementioned factors and job involvement on eudemonic well-being. The moderating role of empathy in these relationships was also investigated in this nested design. The results indicate that behavioral attitudes, perceived control, and job involvement have significant positive effects on volunteers’ eudemonic well-being. A high perspective taking (cognitive empathy) of volunteers positively moderates the relationship between job involvement and eudemonic well-being, while high personal distress (affective empathy) buffers this relationship. The theoretical and practical implications of these findings are discussed in relation to emergency volunteer activities.